Developing mobile learning based on ethnomathematics viewed from adaptive e-learning: Study of two dimensions geometry on Yogyakarta palace’s chariot - Nuryadi Nuryadi; Luky Kurniawan; Isna Kholifa (Association for Scientific Computing Electrical and Engineering(ASCEE), 2020)
This research aims to develop mobile mathematics learning media based on ethnomathematics on the best rectangular view from criteria, validity, practicality, and effectiveness. This research was Research and Development (RD) refers to the developing model of ADDIE. The steps of ADDIE developing models were: (1) analysis, problem analysis and media content analyze; (2) design, made storyboards and flowcharts; (3) development, developing initial products including design planning and design implementation; (4) implementation, reality trials both small and large scale; and (5) evaluation, product revision and final product. Ethno-mathematics elements used in this research were parts of the Yogyakarta Palace’s chariot using the main application named Adobe Flash CS6. The research’s results showed that it has completed: (1) the validity aspect, the material experts got a score 68 with an excellent grade, and the media experts got a score of 73 with an excellent grade; (2) the practicality aspect, with assessors from 32 students getting 2006 of a score with an excellent grade; and (3) the effectiveness aspect, with virtual ability test that has 92,7% of students who completed. So, this mobile learning based on ethnomathematics is appropriated as mathematics learning media through adaptive e-learning on the study of two-dimensions geometry.